2011
DOI: 10.1016/j.seizure.2011.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic drug use during pregnancy: Perinatal outcomes

Abstract: This study demonstrates that the majority of women suffering from epilepsy were treated with monotherapy rather than polytherapy during pregnancy. While most used other agents, an important number of women continued to use valproate in pregnancy despite the long standing evidence of its teratogenicity and increasing evidence of its neuro-toxicity to the fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…Like our study, Kulaga et al 41 also found that the frequency of exposure to anticonvulsant mood stabilisers declined substantially during pregnancy, and in the second trimester was estimated to be 0.22% (95% CI 0.19 to 0.26%). 41 Most women were dispensed anticonvulsant mood stabilisers as monotherapy (79.6%) during pregnancy and the three most prevalent anticonvulsants were carbamazepine (29.9%), valproate (19.7%) and phenytoin (11.5%). 41 To our knowledge there are no recent estimates of lithium usage or prescribing in pregnancy.…”
Section: Psychotropic Medication Prescribed Before During and After supporting
confidence: 83%
See 4 more Smart Citations
“…Like our study, Kulaga et al 41 also found that the frequency of exposure to anticonvulsant mood stabilisers declined substantially during pregnancy, and in the second trimester was estimated to be 0.22% (95% CI 0.19 to 0.26%). 41 Most women were dispensed anticonvulsant mood stabilisers as monotherapy (79.6%) during pregnancy and the three most prevalent anticonvulsants were carbamazepine (29.9%), valproate (19.7%) and phenytoin (11.5%). 41 To our knowledge there are no recent estimates of lithium usage or prescribing in pregnancy.…”
Section: Psychotropic Medication Prescribed Before During and After supporting
confidence: 83%
“…Only between 21% and 25% had an indication of epilepsy. 40 A study by Kulaga et al 41 identified 349 epileptic pregnant women within the Quebec Pregnancy Registry and divided these into three groups based on maternal use of anticonvulsant mood stabilisers during pregnancy. Like our study, Kulaga et al 41 also found that the frequency of exposure to anticonvulsant mood stabilisers declined substantially during pregnancy, and in the second trimester was estimated to be 0.22% (95% CI 0.19 to 0.26%).…”
Section: Psychotropic Medication Prescribed Before During and After mentioning
confidence: 99%
See 3 more Smart Citations